Cyclohexane and phosphorus based benzoxazine-bismaleimide hybrid polymer matrices: thermal and morphological properties. Issue 7 (3rd July 2019) - Karikal Chozhan, C.; Chandramohan, A.; Alagar, M.
Abstract: Benzoxazine monomers namely 1, 1-bis (3-methyl-4-hydroxyphenyl)cyclohexane benzoxazine (CBDDM ) and bis(4-maleimidophenyl) triphenylphosphine oxide benzoxazine (BMPBBAPPPO ) were synthesized and blended with bismaleimide (BMPM) to improve thermal properties of polybenzoxazine. The benzoxazine- bismaleimide (Bz-BMI) hybrid polymer matrices were prepared via in-situ polymerization and their thermal and morphological properties were studied. The chemical reaction of benzoxazines with the bismaleimide was carried out thermally and the resulting product was analyzed by FT-IR spectra. The glass transition temperature, curing behavior, thermal stability, char yield and flame resistance of the hybrid polymer matrices were analyzed using DSC and TGA. The homogeneous structure of the hybrid polymer matrices was determined by SEM and visual observations. Data obtained from thermal studies infer that these hybrid materials possess high thermal stability which can be used as adhesives, sealants, coating and matrices for high performance automobile and microelectronic applications.